1948
DOI: 10.1172/jci101928
|View full text |Cite
|
Sign up to set email alerts
|

Serum Precipitable Iodine Concentrations During Pregnancy 1

Abstract: Circulating thyroid hormone is measured more accurately by determination of serum precipitable iodine than of basal metabolic rate (1 to 8). Since the latter increases during pregnancy (9 to 14) serum precipitable iodines were investigated in 43 pregnant women and followed in some subjects after delivery.'A preliminary report of this investigation was included in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
30
1
1

Year Published

1950
1950
2008
2008

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(36 citation statements)
references
References 18 publications
4
30
1
1
Order By: Relevance
“…Since pregnancy and estrogen administration produce increases in PBI and TBP in the serum, it appears possible that similar alterations might occur in women during the menstrual cycle. Attempts to detect such changes in the PBI revealed no unequivocal cyclic variation (5,38). In the nonpregnant subjects who served as controls for the present study, no significant differences between TBP in men and women were observed (15), but the time of sampling was not correlated with the menstrual cycle.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Since pregnancy and estrogen administration produce increases in PBI and TBP in the serum, it appears possible that similar alterations might occur in women during the menstrual cycle. Attempts to detect such changes in the PBI revealed no unequivocal cyclic variation (5,38). In the nonpregnant subjects who served as controls for the present study, no significant differences between TBP in men and women were observed (15), but the time of sampling was not correlated with the menstrual cycle.…”
Section: Discussioncontrasting
confidence: 57%
“…The thyroid gland may become enlarged and hyperplastic (1,2), thyroidal uptake of radioiodine is increased (3,4), "conversion" of blood iodide to organic form is more rapid (4), and the serum proteinbound iodine (PBI) is elevated (5,6). Although these alterations are like those seen in hyperthyroidism, they appear to be associated, in early pregnancy at least, with an unequivocally euthyroid state.…”
mentioning
confidence: 99%
“…In 1948 it was reported by Heinemann, Johnson and Man (1) that early in pregnancy the precipitable (protein-bound) iodine in the serum (SPI) rose to concentrations in the upper range of normal or even to levels that outside of pregnancy are characteristic of hyperthyroidism. It also appeared that if the SPI did not rise, the pregnancy was likely to end in abortion within the first four months.…”
mentioning
confidence: 99%
“…However, although other objective determinations of thyroid function such as the measurement of the basal metabolic rate or the lipids of the serum are unreliable in acute hepatitis, none of these patients had clinical evidences of hyperthyroidism nor was the course suggestive of this disease. High values of SPI are found also in pregnancy (14), but the cause of the rise in the two conditions seems to be dissimilar inasmuch as the rise occurs in hepatitis only early in the course and is not related to the severity of the disease.…”
Section: Discussionmentioning
confidence: 91%